Exploratory analysis of core soft s for employability in Nigeria’s higher education (2022)
The study did an exploratory analysis of core transferable soft skills for employability in higher education programmes in Nigeria. Transferable soft skills for employability are of more importance in recent times. This is because the practical world requires both relevant knowledge and skills for human survival and productivity. Lots of rivalries abound due to the growing population of potential degree holders with the absence of consummate competencies in accordance with employment opportunities in the highly competitive labour market. This has caused unemployment on a huge scale and has further amounted to other rippling problems. Higher education is evolving and getting diversified but lacks the required competence of the 21st-century world of jobs which is necessary for employability and wealth creation. Several studies have affirmed that higher education in Nigeria has been fundamentally flawed with a wrong learning model. The need for core and transferable soft skills such as research and study skills, self-, time- and people-management, capacity building for managing interpersonal relationships, leading, and influencing others, Information and Communication Technology, financial literacy, and effective decision-making, is of paramount importance. It is a necessity required in higher education for the world of job survival. However, higher education is more vital than most people think because the more highly educated a country is, the more prosperous it becomes. The paper recommended the need for the curricular experience to accommodate the identified core transferable employability soft skills, as well as their application, in life situations.